The Importance of Metabolites in Modulating Insulin Sensitivity - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Metabolism impairment in obese condition usually initially triggered by inflammation and insulin signaling impairment. The involvement of metabolites, including lipids, amino acids, and ketone bodies, in altering insulin sensitivity has been revealed after massive data sets were provided by the studies regarding metabolomics and lipidomics.CONTENT: Metabolites were now understood to serve more than just the metabolism products, but also as active signaling molecules including in insulin and immunological actions. Different lipid metabolites can serve as signaling molecules to induce insulin resistance of sensitivity through a similar pathway, and impact on the inflammation status. Branched Chain Amino Acids (BCAA) and many amino acids have been correlated with mitochondrial dysfunction and insulin impairment. Ketogenic diet, supplementation and microbiota transplantation become the current strategies to set a preferable metabolites composition to modulate insulin sensitivity.SUMMARY: Thousands of metabolites can now be measured using technical and bioinformatics developments. Different types of amino acids, fatty acids, and bile acids are being studied in relation to altered metabolic states, particularly obesity and type 2 diabetes mellitus. A thorough knowledge of the metabolic changes that contribute to insulin resistance might lead to the discovery of new targets for enhancing insulin sensitivity and preventing and treating many metabolic disorders.KEYWORDS: metabolites, insulin resistance, lipids, amino acids, ketone bodies